Prevalence and associated factors of depressive symptoms among disadvantaged adolescents: results from a population-based study in Bangladesh - Nasreen, Hashima E (Malaysian Public Health Physicians' Association, 2016)
PROBLEM: Few studies have examined the adolescents' depression in low-income countries and no research has yet been carried out in Bangladesh. This study estimated the prevalence of depressive symptoms and explored the associated factors and help seeking behavior among adolescents in Bangladesh. METHODS: Data originated from a cross section of 2,440 randomly selected boys and girls aged 13-19 years in a rural district and urban slums of Dhaka city, Bangladesh, during October-November 2012. Beck Depression Inventory (BDI), a 21-item scale, measured the prevalence of depressive symptoms using a cut-off 16 or higher. FINDINGS: The prevalence of depressive symptoms among adolescents was 14%, with predominance in urban slums and among girls. Older age (15-19 years), poverty, and poor parental relation were found to be associated with depressive symptoms of both sexes; family history of depressive symptoms for boys; and reproductive illness and sexual abuse for girls. More than 80% of depressed adolescents sought no help. CONCLUSIONS: Adolescent depressive symptoms are common and largely undetected public health problem in Bangladesh. Policies aimed at concerted efforts for implementing a school-based counseling program with components of cognitive behavioral therapy and developing referral systems for those who scored at least 30 at BDI may ameliorate the potential harmful consequences of depressive symptoms in adolescents.